Oropharyngeal Administration of Mother's Milk Prior to Gavage Feeding in Preterm Infants: A Pilot Randomized Control Trial. Issue 1 (6th May 2019) - Abd‐Elgawad, Mahmoud; Eldegla, Heba; Khashaba, Mohammed; Nasef, Nehad
Abstract: Background: Oropharyngeal administration of mother's colostrum in early days has an immunoprotective effect in preterm infants. Objectives: Our aim was to study the effect of oropharyngeal administration of mother's milk (OPAMM) on decreasing the incidence of nosocomial sepsis. Methods: In a pilot prospective randomized study on preterm (<32 weeks gestation and 1500 g weight) infants, we compared OPAMM practice (applying 0.2 mL of mother's colostrum or milk prior to gavage feeding until full oral feeding is reached) with regular gavage feeding. The primary outcome was incidence of culture‐proven nosocomial sepsis. Secondary outcomes included bacterial colonization of the gastrointestinal tract, feeding intolerance, time to reach full feeding, incidence of necrotizing enterocolitis, ventilator‐associated pneumonia, duration of respiratory support, incidence of bronchopulmonary dysplasia (BPD), length of hospital stay, and neonatal mortality. Results: The outcomes of 200 neonates (100 in each group) were analyzed. OPAMM practice did not significantly reduce the incidence of culture proven nosocomial sepsis (8% vs 13%, P = 0.35). Infants in the OPAMM group had a significantly lower growth of Klebsiella species in the oropharyngeal pouch, borderline lower incidence of ventilator‐associated pneumonia, shorter duration of oxygen therapy, less episodes of feeding intolerance, reached full feeding earlier, and had a shorter length of hospital stay. OPAMM practice did not affect the incidence of necrotizing enterocolitis, BPD, or neonatal mortality. Conclusion: OPAMM prior to gavage feeding does not reduce the incidence of nosocomial sepsis but had beneficial effects on early achievement of feeding, and early hospital discharge in preterm very low‐birth‐weight infants.